KECERDASAN BUATAN DAN LITERASI KRITIS: REFLEKSI HUMANIORA PADA LAYANAN UPT PERPUSTAKAAN DAN PENERBITAN UNIVERSITAS MUHAMMADIYAH MAKASSAR - Maria Ulviani; Siti Suwadah Rimang (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study examines the integration of Artificial Intelligence (AI) into university library services from a humanities perspective, with a focus on critical literacy development. It analyzes how AI technologies—such as generative AI, recommendation systems, and interactive chatbots—support students' and librarians' abilities at Universitas Muhammadiyah Makassar to critically interpret, evaluate, and reflect on information. Employing a qualitative descriptive approach with content analysis, this study draws on literature analysis, document analysis, and semi-structured interviews to identify practices, opportunities, and challenges in implementing AI within library services. The findings indicate that integrating AI with a humanistic approach supports the development of students' critical thinking, ethical reasoning, and evaluative skills while transforming information-seeking and utilization processes from passive activities into reflective learning experiences. The study highlights that AI serves not merely as a technological tool but also as a pedagogical medium that supports critical, ethical, and humanistic literacy. This study contributes by formulating strategies for integrating AI with critical literacy and humanities values while providing practical guidance for academic libraries in balancing technological innovation with educational ethics and reflective learning.